2021
DOI: 10.3389/fpls.2021.655673
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Biocontrol Agents From Microbial Keystone Taxa Associated to Suppressive Soil: A New Attempt for a Biocontrol Strategy

Abstract: Recent studies have observed differing microbiomes between disease-suppressive and disease-conducive soils. However, it remains unclear whether the microbial keystone taxa in suppressive soil are critical for the suppression of diseases. Bacterial wilt is a common soil-borne disease caused by Ralstonia solanacearum that affects tobacco plants. In this study, two contrasting tobacco fields with bacterial wilt disease incidences of 0% (disease suppressive) and 100% (disease conducive) were observed. Through ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
6
37
0
Order By: Relevance
“…Three Pseudomonas strains, P. koreensis HCH2-3, P. rhodesiae MTD4-1, and P. lurida FGD5-2, were previously isolated from the rhizosphere of tobacco plants cultivated in Zunyi city, Guizhou Province, China (Zheng et al, 2021). The Pseudomonas strains were cultivated in Luria-Bertani (LB) medium at 28°C and stored in 20% (v/v) glycerol at −80°C.…”
Section: Bacterial Strains and Growth Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three Pseudomonas strains, P. koreensis HCH2-3, P. rhodesiae MTD4-1, and P. lurida FGD5-2, were previously isolated from the rhizosphere of tobacco plants cultivated in Zunyi city, Guizhou Province, China (Zheng et al, 2021). The Pseudomonas strains were cultivated in Luria-Bertani (LB) medium at 28°C and stored in 20% (v/v) glycerol at −80°C.…”
Section: Bacterial Strains and Growth Conditionmentioning
confidence: 99%
“…All leaf samples were washed with cold distilled water, frozen with liquid nitrogen, and stored at −80°C. The sampling of the rhizosphere soil and roots was as follows: The rhizosphere soil (more than 1 g per sample) which was tightly bound to tobacco roots was obtained with a brush (Zheng et al, 2021), the root was collected by rinsing thoroughly with phosphate-buffered saline (PBS) solution and then soaked in alcohol (75%, v/v) for 1 min and sodium hypochlorite (5%, v/v) for 3 min, and the root was finally rinsed with sterile water for three times (Zheng et al, 2021). All rhizosphere soil, roots, and leaf samples were stored at −80°C prior to DNA or RNA extraction.…”
Section: Rhizosphere Soil Roots and Leaf Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to suppressive soils, a total of 9 and 13 bacterial keystone taxa were identified from suppressive soils against Ralstonia solanacearum , and three species belonging to culturable strains of Pseudomonas showed high 16S rRNA gene similarity (98.4–100%) with keystone taxa [ 153 ]. However, another study showed that the keystone microbiome against Ralstonia solanacearum were comprised of the phyla Actinobacteria and Firmicutes and that these microbiota likely plan an important role in diminishing disease incidence [ 154 ].…”
Section: Core Microbiome—“few But Good”mentioning
confidence: 99%
“…The interactions of pathogens, hosts, and the environment determine the occurrence of plant diseases. The environment, especially soil characteristics, determines the source of microorganisms recruited by plant roots, which mainly affects disease outbreaks (Chiaramonte et al, 2021;Zheng et al, 2021). Diseases that spread through soil are called soil-borne plant diseases, and they adversely affect crop production worldwide, whereas some other types of organic matter might exert beneficial effects that reduce the presence of pathogens such as Fusarium, Phytophthora, Pythium, and Rhizoctonia (Jambhulkar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%